Uma compreensão hermenêutico-filosófica da noção de abordagem centrada na pessoa - BEZERRA, Edson do Nascimento (2018)
ABSTRACT This objective research understands, from the Gadamerian hermeneutic-philosophical point of view, a notion of person-centered approach. From the premise that the person-centered approach is not just an extension of the areas of application of client-centered therapy, justified by the addictions established by John Keith Wood, Rogers' collaborator and co-responsible for the application of the notion, defining what person-centered approach it is not. In this bibliographical research, a philosophical hermeneutics developed by Hans-Georg Gadamer is used to make a critical approach considering its capacity to be directed to the modern biological model and its notion of historical-dialogical capacity that rehabilitates tradition and is carried out in a fusion of horizons. In order to make the proposal effective, the terms therapy and approach are conceptualized and elucidated by exploring the process of passing from a phase identified as Client-Centered Therapy to the Person-Centered Approach phase. To that end, we review the main classifications carried out on the development of Rogers's thinking, with emphasis on those that theoretically legitimize the last phase of his thinking, identified as Person-Centered Approach, when the notion of a person-centered approach was formulated by Carl Rogers and John Keith Wood. It presents a categorial problematization of the terms involved in this process of changing the identity of the rogerian legacy, client and person to subsidize the hermeneutical analysis of the notion of the approach, linking it to the necessary update of the notion of client-centered therapy. We explore the repercussions derived from the analysis, focused on the exercise of hermeneutic understanding of the person-centered approach as a course fulfilled by the researcher. It is verified that the update of the notion of client-centered therapy to a person-centered approach has the dialectical and paradoxical character of overcoming Rogers's universalist project regarding the apprehension of human experience, accompanied by the proposal of preserving his legacy through the radical opening invitation to experience. It is also emphasized, therefore, that the productivity of this change of terms is beyond the mere extension of the areas of application of Rogers' thinking. Finally, possible articulations for future research, linked to the potential of interlocution between the person-centered approach and the Gadamerian philosophical hermeneutics, and to the methodological and epistemological-historiographic limits of the present research are indicated.